Pengaruh Salinitas KCl & NaCl Terhadap Kestabilan Emulsi Minyak Mentah–Air Di Lapangan Bekasap, PT. Chevron Pacific Indonesia - Dhanang Hayuningwang; Ahmad Fadli; Fajril Akbar (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
In the oil well drilling and service process, NaCl and KCl used to provide hydrostatic pressure into the bowels of the earth. Brine solution unintentionally produced to the surface facility when oil lifting process perform and induce thickness of oil-water emulsion at separation tank. The objective of this study was to determine the effect of NaCl and KCl on the oil-water demulsification process at Bekasap field area, PT CPI Duri. This study was conducted by varying salinity of NaCl and KCl by 10%, 20%, 30% and 40% in 100ml oil-water emulsion sample with oil and water ratio 1:1. Demulsification of emulsion sample using precipitation method for 240 minutes, at temperature 60oC and recording increasing the number of free water every 20 minutes. The data obtained from study showed in the graphs indicate that emulsion separation speed tends to be slower due to increase of salt salinity. From the final result after 240 minutes of precipitation shown that emulsion separation process which influenced by NaCl salt is more difficult than the effect of KCl salt.Key words: Brine, Emulsion, Oil, Water,